https://www.qbyte.org/puzzles/p158s.html ]]>

(y+1)^(2k+2)-[y^(2k+3)+1]/(y+1)=(2k+3)y(y^2+y+1)^k ]]>

p=3 x^2 + x + 1 = (x-1)^2 + 3x is composite when x = -3t^2

2p=4 x^2 + 1 = (x+1)^2 – 2x is composite when x=2t^2

p=5 x^4 + x^3 + x^2 + x + 1 = (x^2 + 3x + 1)^2 – 5x(x+1)^2 is composite when x = 5t^2

2p=6 x^2 – x + 1 = (x+1)^2 – 3x is composite when x = 3t^2

p=7 (x^7 – 1)/(x-1) = (x-1)^6 + 7x (x^2 – x + 1)^2 is composite when x = -7t^2

For the problem at hand, 2p=14, and (x^7+1)/(x+1) is composite when x=7t^2

]]>The same idea doesn’t seem to work.

]]>